Genomic epidemiology of nontoxigenic Corynebacterium diphtheriae from King County, Washington State, USA between July 2018 and May 2019. Issue 12 (4th December 2020) - Xiaoli, Lingzi; Benoliel, Eileen; Peng, Yanhui; Aneke, Janessa; Cassiday, Pamela K.; Kay, Meagan; McKeirnan, Shelly; Duchin, Jeffery S.; Kawakami, Vance; Lindquist, Scott; Acosta, Anna M.; DeBolt, Chas; et al.
Abstract : Between July 2018 and May 2019, Corynebacterium diphtheriae was isolated from eight patients with non-respiratory infections, seven of whom experienced homelessness and had stayed at shelters in King County, WA, USA. All isolates were microbiologically identified as nontoxigenic C. diphtheriae biovar mitis. Whole-genome sequencing confirmed that all case isolates were genetically related, associated with sequence type 445 and differing by fewer than 24 single-nucleotide polymorphisms (SNPs). Compared to publicly available C. diphtheriae genomic data, these WA isolates formed a discrete cluster with SNP variation consistent with previously reported outbreaks. Virulence-related gene content variation within the highly related WA cluster isolates was also observed. These results indicated that genome characterization can readily support epidemiology of nontoxigenic C. diphtheriae .